35.3k views
5 votes
I don’t understand :( help?

I don’t understand :( help?-example-1

2 Answers

2 votes

Answer:

x = 5

Explanation:

1. First we need to simplify both sides of the equation.

( 3 )( x ) + ( 3 )( 1 ) = 18 Distribute the equation.

= 3x + 3 = 18

2. Now subtract 3 from both sides.

3x + 3 − 3 = 18 − 3

3x = 15

3. Now divide both sides by 3.

3x/3 = 15/3

x = 5

User Jadie
by
5.5k points
3 votes

Answer:

X = 5

Explanation:

To find the solution to a problem like this remember the order of PEMDAS.

According to pemdas parenthesis comes first, do you would solve for this part of the equation by multiplying the outer number by each side inside the parenthesis

Aka 3 × X and 3 × 1

This would make your new equation

3x + 3 = 18

Then, you would try to shorten the equation by removing or adding something to both sides.

In the given equation that would be subtracting 3 by either side, leaving over

3x = 15

Lastly, to find X you would divide 3x and 15

3 ÷ 15 = 5

Therefore X = 5

User Kornelius
by
4.8k points